Case Study: Analysis of Nursing Care With The Application Of Guided Imagery Therapy To Overcome Delusions Of Suspicion In Patients In The Flamboyant Ward Of Menur Mental Hospital Surabaya - Atika Jatimi (Universitas Negeri Surabaya, 2026)
Delusions are false beliefs resulting from impaired judgment of reality, inconsistent with the individual's intellectual level and cultural background, and persist despite being contrary to facts and common sense. Delusions cannot be corrected and often occur in patients with mental disorders, one of which is delusions of suspicion. This study aims to apply psychiatric nursing care through guided imagery therapy to address the nursing problem of delusions of suspicion. This study used a descriptive design with a case study approach that illustrates the comprehensive nursing care management process. The subject was one patient with a nursing diagnosis of delusions of suspicion. The study was conducted at Menur Mental Hospital (RSJ) Surabaya, East Java, over three weeks. Data collection was conducted through a comprehensive nursing assessment, determination of the nursing diagnosis, formulation of interventions, implementation of nursing actions, and evaluation of nursing care outcomes. The case study results indicate that Mrs. N experienced a nursing problem of suspicious delusions. After receiving guided imagery therapy, her Positive and Negative Syndrome Scale (PANSS) score decreased from 92 to 76. Guided imagery therapy is a relaxation method that involves imagining pleasant situations to provide positive physical, emotional, and spiritual effects. The application of this therapy has been shown to help reduce the intensity of suspicious delusions in clients with mental disorders.